2021
DOI: 10.5556/j.tkjm.52.2021.3280
|View full text |Cite
|
Sign up to set email alerts
|

Bounds for Generalized Distance Spectral Radius and the Entries of the Principal Eigenvector

Abstract: For a simple connected graph $G$, the convex linear combinations $D_{\alpha}(G)$ of \ $Tr(G)$ and $D(G)$ is defined as $D_{\alpha}(G)=\alpha Tr(G)+(1-\alpha)D(G)$, $0\leq \alpha\leq 1$. As $D_{0}(G)=D(G)$, $2D_{\frac{1}{2}}(G)=D^{Q}(G)$, $D_{1}(G)=Tr(G)$ and $D_{\alpha}(G)-D_{\beta}(G)=(\alpha-\beta)D^{L}(G)$, this matrix reduces to merging the distance spectral and distance signless Laplacian spectral theories. In this paper, we study the spectral properties of the generalized distance matrix $D_{\alpha}(G)$.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…We know that Tr i � k and T i � k 2 . According to Lemma 1, k is the largest eigenvalue of D α (G), and ρ(D α (G)) � k, so the equality holds in (15). On the contrary, if inequality ( 15) is equal, then x 1 � x 2 � .…”
Section: Somentioning
confidence: 98%
See 1 more Smart Citation
“…We know that Tr i � k and T i � k 2 . According to Lemma 1, k is the largest eigenvalue of D α (G), and ρ(D α (G)) � k, so the equality holds in (15). On the contrary, if inequality ( 15) is equal, then x 1 � x 2 � .…”
Section: Somentioning
confidence: 98%
“…In particular, they showed that this upper bound is better than the upper bound obtained by Cui et al In [14], the authors established the relations between the smallest eigenvalues of D α (G), D(G), and D Q (G) and obtained sharp bounds for the smallest eigenvalue λ n of D α (G) in terms of various graph parameters. In [12,[15][16][17], Alhevaz et al established some new sharp bounds for the generalized distance spectral radius of G by using diferent graph parameters and characterized the extremal graphs. Ten, they obtained new bounds for the k-th generalized distance eigenvalue.…”
Section: Introductionmentioning
confidence: 99%